A puriﬁed lectin with larvicidal activity from a woodland mushroom, Agaricus semotus Fr. - Adedoyin, Isaiah O.; Adewole, Taiwo S.; Agunbiade, Titilayo O.; Adewoyin, Francis B.; Kuku, Adenike (Acta Biologica Szegediensis, 2021)
This study investigated the larvicidal activity on Culex quinquefasciatus of lectin purified from fresh fruiting bodies of woodland mushroom, Agaricus semotus. A. semotus lectin (ASL) was purified via ion-exchange chromatography on DEAE-cellulose A-25 and size exclusion chromatography on Sephadex G-100 matrix. Molecular weight (16.6 kDa) was estimated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The eﬀects of temperature, pH, metal chelation- and larvicidal activity of ASL were also investigated. The ASL indiﬀerently agglutinated the erythrocytes of the human ABO blood system and was stable at acidic pH and below 50 °C whereas 66% of its activity was lost at 60 °C with complete inactivation at 70 °C. ASL is a metalloprotein requiring barium ion as chelation of metals by 50 mM EDTA rendered the lectin inactive, while the addition of BaCl2, among other metal salts, restored the activity. ASL showed larvicidal activity against C. quinquefasciatus larvae after 24 h with a mortality of 5 and 95% at 5 and 25 mg/mL respectively, and LC50 of 13.80 mg/mL. This study concluded that purified A. semotus lectin showed impressive larvicidal activity, which could be exploited in its development as an insecticidal agent.